Evaluating growth and wood prouductivity of Pinus brutia Ten in Al Rastin site -Lattakia. - عماد قبيلي; وائل علي; نغم علاّن (Latakia University Journal -Biological Sciences Series, 2022)
This study aimed to evaluate the growth and wood prouductivity of brutia pine (Pinus brutia Ten.) at age 39 years in Al Rastin site - Lattakia. 13 circle plots (with area size of 400 m²) in the study area were sampled, both of diameter at breast height and crown width of all trees in this plots were measured, appropriate methods were used to estimate both of total above ground biomass and wood volum. an amount of 178.4 ton/ha and 197.2 m3/h were assumed for total biomass and wood volum respectively, mean annual increment was 5.07 m3/h/year. The basal area estimated by 22.2 m2/h at 653 trees per hectar, the mean of tree diameters and heights were calculated by 19.5 cm and 16.2 m respectively. Parabel equation was the best fit of estimating of tree height by the determinant factor of 0.70 = R².